2021
DOI: 10.1080/13506285.2021.1976892
|View full text |Cite
|
Sign up to set email alerts
|

Gender and perceived cooperation modulate visual attention in a joint spatial cueing task

Abstract: This research investigated how interactive social contexts shape basic visual attention. It has been shown that social information can modulate inhibition of return effects in joint spatial cueing tasks. We predicted that if perceptions of cooperativeness explain this phenomenon, we would then observe larger inhibition of return effects for more cooperative individuals and in highly cooperative contexts. Experiments 1a and 1b found larger inhibition of return effects and greater perceptions of cooperativeness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In that study, just as in the present one, differences in participants' attention cannot be attributed to the physical environment but to the way in which participants mentally represented that environment (Gobel et al, 2018; also see Richardson & Gobel, 2015). Further recent studies by the same authors (Gobel & Giesbrecht, 2020;Tufft & Gobel, 2022) also indicated that social top-down information can affect lowlevel spatial orienting.…”
Section: The Sociality Of the Social Iormentioning
confidence: 81%
“…In that study, just as in the present one, differences in participants' attention cannot be attributed to the physical environment but to the way in which participants mentally represented that environment (Gobel et al, 2018; also see Richardson & Gobel, 2015). Further recent studies by the same authors (Gobel & Giesbrecht, 2020;Tufft & Gobel, 2022) also indicated that social top-down information can affect lowlevel spatial orienting.…”
Section: The Sociality Of the Social Iormentioning
confidence: 81%
“…The second was previous studies examining similar effects (i.e., the social inhibition of return). Some of these studies conducted a two-way ANOVA and employed approximately 35 participants per group (e.g., Gobel & Giesbrecht, 2020 ; Tufft & Gobel, 2022 ). Considering these two types of studies, it was assumed that an effect size for the present study’s hypothesis could be examined with 40 participants per group.…”
Section: Experiments 2bmentioning
confidence: 99%
“…In many ways, it does. Recent work has shown that covert attentional orienting (shifting attention without gaze movements) is sensitive to the social significance of the cue, including its association with another individual (Nafcha et al., 2020), a person's gender (Tufft & Gobel, 2022), and their status and actions (Gobel et al., 2018). Similarly, people follow more easily and spontaneously the gaze direction of people who present some type of social relevance, either via facial/physical cues like dominance (Jones et al., 2010), behavioral cues like group cooperation (Hudson et al., 2012), and personal information like high‐status CVs (Dalmaso et al., 2012).…”
Section: Attentional Orientingmentioning
confidence: 99%